Cultural Interpretation and Traditional Perspectives in Ahmed Yerima’s Akudaaya - Ojediran, Oludolapo; Arinde, Tayo Simeon; Daniel, Taye Mary; Adeola, Taye Shola; Magbagbeola, Olayinka; Adenola, Tomiwa (Journal of Ecohumanism, 2024)
Culture remains a clear indicator of the organic identity of mankind. Cultural materials are therefore one of the dominant sources from which playwrights have continued to draw. However, an attempt to dramatise certain inherent cultural practices of a people often comes with challenges especially for a playwright who does not belong to such culture. Hence, this study examines Ahmed Yerima’s Akudaaya with the view to define the cultural trajectories and traditional dispositions reflected in the play. Through textual analysis, the study analyses the selected play-text. It is revealed that Ahmed Yerima’s attempt to reflect the cultural identity and traditional perspectives of the Yoruba people is manifested in his dramatisation of the symbolic representation of the king’s crown; the cultural interpretation of akudaaya and the dichotomy of language; cultural norms and the significant position of Iyalode; ritual aesthetics and the spirito-cosmic identity of the Yoruba people. The study concludes that Ahmed Yerima’s Akudaaya remains one of the notable plays written by a Nigerian playwright which reflects the cultural identity of the akudaaya view among the Yoruba people. However, Yerima is able to achieve cultural reconstruction and initiate a challenge to create cultural consciousness through his play-text.